РОЗРАХУНКОВА ОЦІНКА ВІБРОПЕРЕМІЩЕНЬ І МЕХАНІЧНИХ НАПРУЖЕНЬ ІЗОЛЯЦІЇ ЛОБОВОЇ ЧАСТИНИ ОБМОТКИ СТАТОРА ПОТУЖНОГО ТУРБОГЕНЕРАТОРА - Кучинський, К.А.; Крамарський, В.А. (Інститут електродинаміки Національної академії наук України, 2022)
Presented are the results of numerical studies of the distribution of vibration displacements and mechanical stresses in the insulation of the frontal part of the stator winding of a powerful turbogenerator under the influence of electrodynamics forces for different constructive solutions of the groove fastening of the winding rods in the end zone of the generator stator core. Modeling of mechanical processes is carried out using the finite element numerical method (FEM) in a two-dimensional setting. The possibility of improving the design with the aim of reducing the amplitude of oscillations of the front parts of the stator winding was considered. Ref. 16, fig. 7.